Electronic Banking and Product Features in Improving Customer Satisfaction and Loyalty - Mersiana Setiarini (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The era of globalization is no longer merely a discourse in the business world. The implementation of the ASEAN Economic Community (AEC) in 2020 is one manifestation of this. With the AEC in place, business competition among companies has become increasingly intense, not only among local companies but also with firms across Southeast Asia. This heightened competition requires all companies to be more aggressive. This study aims to identify, analyze, and test the quality of electronic banking services and product features and examine their impact on customer satisfaction and their implications for banks. The research method employed is a combination of descriptive and verification analysis. Data collection methods include interviews using questionnaires, observation techniques, and literature reviews. The sampling technique used is cluster random sampling, with field data collection conducted in 2022. The data analysis technique involves Structural Equation Modeling (SEM). The study’s findings indicate that, overall, the quality of electronic banking services, product features, customer satisfaction, and loyalty range from poor to good. There is a significant influence of electronic banking service quality and product features on customer satisfaction, both simultaneously and partially. Furthermore, customer satisfaction has a direct impact on the loyalty of savings customers.